The prevention principle in international environmental law / Leslie-Anne Duvic-Paoli, King's College London. - Duvic-Paoli, Leslie-Anne (Cambridge Studies on Environment, Energy and Natural Resources Governance., 2018)
Prevention is recognized as a cornerstone of international environmental law, but this principle remains abstract and elusive in terms of exactly what is required of states to prevent environmental harm. In this illuminating work, Leslie-Anne Duvic-Paoli addresses this issue by offering a systematic, comprehensive assessment in which she clarifies the rationale, content, and scope of the prevention principle while also placing it in a wider legal context. The book offers a detailed analysis of treaty law, custom codification works, and case law before culminating in a conceptualization of prevention based on three definitional traits: 1. Its anticipatory rationale; 2. Its due diligence content; and 3. Its wide spatial scope to protect the environment as a whole. This book should be read by anyone seeking to understand the evolving principle of prevention in international environmental law, and how it increasingly shares common ground with reparation in the arena of compliance control.